2020
DOI: 10.1037/lhb0000359
|View full text |Cite
|
Sign up to set email alerts
|

Policy and procedure recommendations for the collection and preservation of eyewitness identification evidence.

Abstract: Theoretical vs. empirical discriminability: The application of ROC methods to eyewitness identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
428
3
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(444 citation statements)
references
References 273 publications
(337 reference statements)
11
428
3
2
Order By: Relevance
“…The results of conducting extensive research on these issues have led to incorporation of a series of evidence‐based practices that may help mitigate such errors. For example, psychological researchers have found that changes to eyewitness identification procedures—double‐blind administration, specific witness instructions, proper lineup construction, and so forth—may reduce the likelihood that witnesses mistakenly pick the wrong person out of a lineup or photo array (Wells et al., ; Wells, et al., ). Furthermore, interrogation experts have recommended changes such as limiting the length of interrogation sessions (e.g., Bull, ; Leo, ) and video‐recording interrogations as measures to reduce the likelihood of excessive coercion and help guard against false confessions (Kassin et al., ).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…The results of conducting extensive research on these issues have led to incorporation of a series of evidence‐based practices that may help mitigate such errors. For example, psychological researchers have found that changes to eyewitness identification procedures—double‐blind administration, specific witness instructions, proper lineup construction, and so forth—may reduce the likelihood that witnesses mistakenly pick the wrong person out of a lineup or photo array (Wells et al., ; Wells, et al., ). Furthermore, interrogation experts have recommended changes such as limiting the length of interrogation sessions (e.g., Bull, ; Leo, ) and video‐recording interrogations as measures to reduce the likelihood of excessive coercion and help guard against false confessions (Kassin et al., ).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Guidelines in the United States recommend a minimum of five fillers (Technical Working Group for Eyewitness Evidence, ; Wells et al, ) and most police agencies appear to conform to this practice, however some agencies have reported only using two fillers whereas others use as many as 11 (Police Executive Research Forum, 2013). The variability across jurisdictions is reasonable given the lack of consistent empirical evidence to inform policymakers about what the optimal filler number should be.…”
Section: Diagnostic Feature‐detection Prediction Concerning Showups Amentioning
confidence: 99%
“…Studies should carefully manipulate and pilot‐test the similarity of composites to designated suspects in TA lineups, and analyze mix‐ups, rather than simply reporting hits and filler identifications in TP lineups. In line with current identification practice recommendations, post‐decision confidence should be assessed immediately after an identification decision, and the whole procedure should be videotaped (Sporer, 1992b; Wells et al, 2019). Analyses should focus on responses by choosers, and newer confidence calibration analyses and CAC curves could also be considered for analysis (Brewer, Weber, & Guerin, 2019; Mickes, 2015; Wixted & Wells, 2017).…”
Section: Discussionmentioning
confidence: 99%